2012
DOI: 10.1002/chem.201200083
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of Indole‐Derived Allocolchicine Analogues Exhibiting Strong Apoptosis‐Inducing Activity

Abstract: A series of novel pyrrolo-allocolchicine derivatives (containing a 1-methyl-1H-indol-5-yl moiety replacing ring C) was synthesized. The tetracyclic ring system was constructed by Suzuki-Miyaura cross-coupling of a 1-methylindole-5-boronate with an ortho-iodo-dihydrocinnamic acid derivative and subsequent intramolecular Friedel-Crafts acylation. After reduction of the resulting ketone, the nitrogen functionality was introduced in a Mitsunobu-type reaction by using zinc azide followed by LiAlH(4) reduction. Str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 72 publications
0
20
0
Order By: Relevance
“…The geometric parameters of 20 and 34 were found to be considerably different. The dihedral angle between aromatic fragments A and B (see Figure 4) was determined as 43.0° for 20 and 32.3° for 34 , relative to 54° for colchicine ( 1 )45 and 47° for 7 (X = O) 9. These data suggest that compound 34 does not meet the basic structural requirements for interaction with the colchicine binding site of tubulin,3d whereas 20 shows structural similarity with highly active 7 (X = O).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The geometric parameters of 20 and 34 were found to be considerably different. The dihedral angle between aromatic fragments A and B (see Figure 4) was determined as 43.0° for 20 and 32.3° for 34 , relative to 54° for colchicine ( 1 )45 and 47° for 7 (X = O) 9. These data suggest that compound 34 does not meet the basic structural requirements for interaction with the colchicine binding site of tubulin,3d whereas 20 shows structural similarity with highly active 7 (X = O).…”
Section: Resultsmentioning
confidence: 98%
“…Dauban, Dodd, and co‐workers synthesized a series of C5‐alkylated indolobenzazepinones (for instance compound 5 ) related to allocolchicine ( 2 ), some of which exhibited potent antimitotic activity across a wide panel of cancer‐cell lines. In the course of our own research into colchicinoids, we recently described the synthesis of indole‐derived allocolchicine analogs 6 and 7 9. These compounds exhibited strong antiproliferative and apoptosis‐inducing activities (at nanomolar or even sub‐nanomolar concentrations) against Burkitt‐like lymphoma (BJAB) cells, although their unspecific cytotoxicity was found to be particularly low.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, our group reported on the synthesis and biological evaluation of a series of heterocyclic allocolchicine congeners (for instance 3 and 4; Figure 1), in which ring C of the parent compound 2 is replaced by an indole 28,29 or a benzofurane 30 pharmacophore. 28 Herein, we report on the synthesis of pyrrolo-allocolchicinoids of type 5, i.e. 28 Herein, we report on the synthesis of pyrrolo-allocolchicinoids of type 5, i.e.…”
Section: An Alkaloid Isolated From Plants Of the Genusmentioning
confidence: 99%
“…Several structurally related compounds, such as allocolchicine ( 2 ), ( Z )‐stilbenes, 4‐arylcoumarins, and related compounds, were shown to exhibit pronounced cytotoxic effects (Figure ). In this context, we recently demonstrated that compounds 3 and rac ‐ 4 , with an extra furan or pyrrole unit annealed to ring C of the allocolchicine skeleton, exhibit unique antitumor activity …”
Section: Introductionmentioning
confidence: 99%
“…Notably, furano‐allocolchicinoid 3 inhibits tumor growth in mice without noticeable negative neurological symptoms, weight loss, or lethality of experimental animals . (Racemic) pyrrolo‐allocolchicinoid rac ‐ 4 demonstrated a high level of proliferation inhibition and apoptosis induction against different lymphoma cells, whereas its unspecific cytotoxicity is relatively low …”
Section: Introductionmentioning
confidence: 99%